Self-Attitude and Emotional Experiences as a Factor of Personality Hardiness - Chanchikov, Illia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article is devoted to the theoretical and empirical research of the relationship between self-attitude and emotional experiences, and the hardiness of the individual. Hardiness is seen as an integral characteristic of personality that has a connection with the individual properties of the individual at every level of the individual. The study involved 147 people of all ages. The following diagnostic methods were used: Stolin-Panteleev self-attitude questionnaire, test "Scale of differential emotions" K. Izard, S. Muddy’s hardiness test (adaptation by D. O. Leontiev, O. I. Raskazova). The analysis of the results of the self-attitude survey showed that the indicator "Global self-attitude" in the subjects is at a high positive level. Components of self-attitude such as "Self-interest" and "Self-understanding" also scored the most points. The research of the emotional sphere showed the presence of different types of emotions, both positive and negative in the emotional life of the subjects. Correlation analysis revealed the existence of a link between self-attitude and emotional experiences. The results of the research of hardiness showed the development of this characteristic within the average values. Correlation analysis (Pearson’s correlation coefficient) showed a high level of correlation between the indicators of self-assessment "Global self-attitude" and "Self-esteem" with hardiness, and also inverse correlations between «Acute negative emotions», «Anxious and depressive emotions» and hardiness. The weakest relationship with hardiness was observed in the scale "Attitude of others". Regression analysis allowed us to build a model that explained the high level of dispersion of hardiness. This model includes components of self-attitude and emotional experiences: "Self-esteem", "Self-interest", «Anxious and depressive emotions», "Attitudes of others", "Self-foam". Among these components, the level of hardiness is most affected by "Self-esteem". Research has shown that there is a link between self-attitude, emotional experiences and hardiness. Also was shown that self-attitude and emotional experiences affects the level of hardiness.